(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
Maintaining a positive reputation is essential for businesses and individuals to float in today’s competitive business environment. However, even the most reputable organizations may encounter challenges that lead to negative publicity or a damaged reputation. Whether it’s a public relations crisis, customer complaints, or unfavorable reviews online, addressing these issues promptly and effectively is crucial to mitigating their impact and rebuilding trust.